Rechtssprachliche Kommunikation Im Kontext von Zivilrecht, EU-Recht, Rechtsvergleichung und schiedsrichterlichem Verfahren - Landbrecht, Johannes (Mohr Siebeck, 2023)
Lawyers from different jurisdictions speak different native as well as different legal languages. Understanding one another without burdensome translation exercises is nevertheless possible - if the parties observe and make good use of their legal languages structural similarities and differences.
PublicationDate: 20230330
Keywords: Systemtheorie -- Early Christian Theology -- Rechtslinguistik -- Gospel Studies -- American History -- Luhmann -- Hoeneß -- § 443 Abs. 1 BGB -- Rechtspraxis -- Rechtsübersetzung -- Love in John -- Rechtstheorie -- Internationales Privatrecht -- Zivilverfahrensrecht, Insolvenzrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung